Thyroid Function Abnormalities in Patients with Chronic Kidney Disease - A, K Al Miraj; Magfur, Rahman; Anwarul, Hoque Faraji; Muhammad, Abduz Zaher; Mohammad, Ata Ullah (Journal of Nephrology Advances, 2022)
The function of the thyroid gland is one of the most important in the human body as it regulates the majority of the body's physiological actions. The thyroid produces hormones (T3 and T4) that have many actions including metabolism, development, protein synthesis, and the regulation of many other important hormones. There is a lot of interaction between the kidney and thyroid gland during the disease States thyroid hormones have a major role in regulating the glomerular filtration rate through its hormonal actions in normal physiology. But these things are altered in the disease States such as chronic kidney disease. It is a well-known fact that hypothyroidism causes decreased Glomerular filtration rate whereas hyperthyroidism causes increased Glomerular filtration rate leading to renin-angiotensin-aldosterone system activation. In our study we aim to see the prevalence of low T3 syndrome in different stages of CKD which is a state of physiological benefit in preserving the proteins lost through the Kidneys in CKD patients and since CKD is progressed in hyperthyroidism state it is a protective mechanism in restoring the CKD status. Other subclinical hypothyroidism hyperthyroidism. Autoimmune hypothyroidism. Glomerulonephritis are all part of a dynamic endocrine and nephrology sequence. Thorough knowledge of these is required for optimum treatment of thyroid in CKD patients.
Keywords: Glomerular Filtration Rate; Chronic Kidney Disease; Thyroid Stimulating Hormone.